A noninvasive monitoring device for anesthetics in fish - Power, Deborah (2014)
A noninvasive device capable of recording both gill and lateral fin movements was assembled and used to analyze initial and post-treatment activity frequency (Hz) in fish exposed to anesthetics. Exposure of platy fish (Xiphosphorus maculatus) to saponins from quillaja bark (0.185 mM and 0.555 mM) initially caused hyperactivity, but within five minutes all activity ceased and the fish failed to recover. In contrast, clove oil (67 μg/L) added to water at 22oC reduced activity by 22.8% ± 8.9% (P = 0.038) after 125 ± 19 sec, a sedative effect that was totally reversible. Cinnamon oil compared with clove oil had a significantly longer time to sedation (125 ± 19 versus 235 ± 24 sec, P = 0.02), although no significant difference in the decline in activity was noted.